Combatting voter ignorance: a vertical model of epistocratic voting. (2nd November 2017) - Chou, Mark
ABSTRACT: In light of recent political events, prominent scholars have argued that voters ignorant of the issues should be disqualified from taking part in decisions that have the potential to alter political landscapes. As convincing as this literature is in highlighting voter ignorance, it fails to differentiate between local, state, and federal elections and how levels of political knowledge are often scale-dependent. If the level of median voter ignorance is not uniform from one level of government to the next, then neither can the reforms proposed to combat it. In this article, I adapt Bell's vertical model of democratic meritocracy to argue that the larger the election, the more complex the issues, the more explicit the epistocratic safeguards needed.